Pengembangan Sistem Informasi Layanan Surat Pemerintah Pada Desa Sumput Menggunakan Waterfall Model - Siti Saudah Warsiono; Ismiarta Aknuranda; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sumput Village is located in Sidoarjo City with a large population, so that there is often a demand for public services. One of the public services is the public service request for government letters, this service is still done conventionally / manually. The negative impact are, unregulated service, takes a long time, allows the occurrence of errors (writing data), not well documented datas (data lost / damaged). Many villagers find it difficult to administer these important documents. In order to improve public services for the better, information systems are needed to overcome these problems. The development of this information system uses the Waterfall Model method, which is a systematic approach to software development. The Waterfall Model is used because the business process regarding the service for requesting government letters manually has been determined by the village hall agency. The output of this research is the government mail service information system by applying 4 main stages, namely requirements analysis and definition, system and software design, implementation and unit testing, and integration and system testing. After developing a government mail service information system functional and nonfunctional testing was carried out. Functional testing in the form of validation test with 93% results and nonfunctional testing in the form of browser compatibility using sortsite software with results found 2 critical issues and 1 major issues. Then it can be concluded that this information system is feasible to use.